Incidence and relative survival of melanoma in children and adolescents in the Netherlands, 1989–2013. (10th April 2018) - Eggen, C.A.M.; Durgaram, V.V.L.; van Doorn, R.; Mooi, W.J.; Pardo, L.M.; Pasmans, S.G.M.A.; Hollestein, L.M.
Abstract: Background: Melanoma is rare in the first two decades of life. Trends in incidence differ across countries. Objective: To describe incidence and relative survival of children and adolescents with melanoma in the Netherlands for children (0 through 11 years) and adolescents (12 through 19 years) separately. We hypothesized that adolescent melanoma increased in contrast to childhood melanoma, possibly due to a difference in cancer biology and sun exposure patterns. Methods: Data on all patients of 0–19 years diagnosed between 1989 and 2013 with histologically confirmed cutaneous invasive melanoma were retrieved from the Netherlands Cancer Registry (NCR). Incidence trends were analysed with Joinpoint regression. Relative survival analysis was performed. Results: Between 1989 and 2013, 80 children and 544 adolescents with melanoma were registered in the NCR. Median age at diagnosis was 17 years (IQR 15–18); the female‐to‐male ratio was 1.7 : 1 Statistically significant incidence trends were found in the older age group (12–19 years): an increasing incidence since 1991 [annual percentage change (APC) 3.2%, 95%CI 1.3–5.1] followed by a decrease from 2005 to 2013 (APC −4.9%, 95%CI −9.6–0.0). No incidence trends for childhood melanoma were observed (APC 0.3%, 95% CI −3.0–3.8). Relative survival at 1, 5 and 10 years was 98% (95% CI 97–99), 94% (95% CI 92–96) and 90% (95% CI 87–92), respectively. Survival was worse in males and higher Breslow thickness. Conclusions: Melanoma is very rare under the age of 12 with stable incidence rates. In comparison with childhood melanoma, melanomas in adolescents are more common with a decreasing trend in the past decade. Male sex and increasing Breslow thickness are associated with worse survival in paediatric melanoma patients.